Development of a Gambling Addictive Behavior Scale for Adolescents in Korea - Park, Hyun Sook; Jung, Sun Young (Journal of Korean Academy of Nursing, 2012)
This study was conducted to develop a gambling addictive behavior scale for adolescents. The process involved construction of a conceptual framework, initial item search, verification of content validity, selection of secondary items, and extraction of final items. The participants were 299 adolescents from two middle schools and four high schools. Item analysis, factor analysis, criterion validity, internal consistency, and ROC curve were used to analyze the data. For the final scale, 25 items were selected, and categorized into 4 factors which accounted for 54.9% of the total variance. The factors were labeled as loss of control, life dysfunction from gambling addiction, gambling experience, and social dysfunction from problem gambling. The scores for the scale were significantly correlated with addictive personality, irrational gambling belief, and adolescent's gambling addictive behavior. Cronbach's alpha coefficient for the 25 items was .94. Scale scores identified adolescents as being in a problem gambling group, a non-problem gambling group, and a non-gambling group by the ROC curve. The above findings indicate that the gambling addictive behavior scale has good validity and reliability and can be used with adolescents in Korea.